General Microbiology Lab Report Staphylococcus Testing - Ni Kadek Mia Wulanika (Publikasi Indonesia, 2026)
Food contamination caused by pathogenic microorganisms remains a significant public health concern, particularly due to the presence of Staphylococcus aureus, a bacterium capable of producing toxins that may cause foodborne illnesses. This study aimed to determine the number of Staphylococcus bacterial colonies in food samples, evaluate their safety based on the maximum microbial contamination limits established by the Indonesian Food and Drug Authority (BPOM), and identify the presence of Staphylococcus aureus through catalase testing. The examination was conducted using chicken satay, chicken intestine satay, goat satay, meatballs, shredded chicken, and rendang samples. The samples were serially diluted using sterile water, inoculated onto Mannitol Salt Agar (MSA) medium using the pour plate method, incubated at 37°C for 24 hours, and subsequently analyzed through colony enumeration and catalase testing. The results showed variations in bacterial contamination levels among the tested samples. Chicken satay, chicken intestine satay, and goat satay exceeded the permitted microbial contamination limits, with colony counts of 135.2 × 104 CFU/mL, 49.4 × 104 CFU/mL, and 90 × 103 CFU/mL, respectively, and exhibited positive catalase reactions, indicating the presence of Staphylococcus spp. Meanwhile, meatballs, shredded chicken, and rendang met the safety requirements based on BPOM regulations. Positive catalase reactions were characterized by the formation of oxygen bubbles after exposure to hydrogen peroxide, confirming the presence of catalase-producing bacteria. These findings highlight the importance of proper sanitation, hygienic food handling practices, and microbial quality control to prevent foodborne diseases associated with Staphylococcus aureus contamination.